Intramural Ventricular Recording and Pacing in Patients With Refractory Ventricular Tachycardia: Initial Findings and Feasibility With a Retractable Needle Catheter. (October 2015) - AbdelWahab, Amir; Stevenson, William; Thompson, Kara; Parkash, Ratika; Gray, Christopher; Gardner, Martin; Sapp, John
Abstract : Background—: Ablation of ventricular arrhythmias (VA) can be limited by intramural substrate not amenable to endocardial or epicardial ablation. Feasibility of irrigated needle ablation has been shown, but optimal means of identifying targets is not clear. We analyzed intramural needle electrograms in relation to endocardial electrograms. Methods and Results—: Eight sequential patients (mean age, 56 years) who had failed 1 to 4 prior ablations underwent irrigated needle ablation were included. At selected sites, the needle was advanced into the myocardium. Bipolar and unipolar electrograms from the needle and catheter tip were analyzed. The needle was deployed at 75 sites with suspected intramural substrate among 2309 mapping sites. Intramural bipolar electrogram amplitude and duration correlated closely with endocardial electrograms, but were greater in amplitude and duration (1.5±1.4 versus 0.6±0.5 mV and 131±66 versus 112±51 ms; P =0.001 for both). During sinus rhythm intramural late potentials tended to be more common than endocardial late potentials (53.6% versus 35.7%; P =0.12). Intramural electrograms during VA preceded endocardial electrograms (−29±34 versus −15±21 ms; P =0.001). Irrigated needle ablation terminated VA at 12 of 28 sites with ablation during VA. Termination site needle electrograms tended to be earlier than nontermination sites (−54±37 versus −36±33 ms pre-QRS; P =0.15). Pacemapping from the needle at 19 sites matched the VA at 18 and showed stimulus to QRS of 60±51 ms. Conclusions—: Recordings from intramural needle may be useful for selecting ablation targets during ventricular tachycardia and for substrate mapping. Further study is needed to develop methods to guide selection of optimal sites for needle deployment and ablation.